2006
DOI: 10.1111/j.1469-7610.2005.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Event rate and event‐related potentials in ADHD

Abstract: The association between the steeper increase in RT and reduced parietal P3s may indicate that the children with ADHD did not allocate enough extra effort to adjust to a potentially under-activated state. However, the event rate effects could not account for all of the differences between groups and also early automatic information processing stages seem disturbed in this disorder as indexed by larger P2 amplitudes. Alternative explanations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 44 publications
12
106
3
8
Order By: Relevance
“…The response inhibition (Barkley, 1997;Quay, 1997) and cognitive energetic models (Sergeant, 2000;Sergeant, 2005) have lent themselves readily to consideration using ERP tasks/methodology. Studies examining the effect of energetic factors on inhibitory processing report at least partial support for the Cognitive Energetic Model (Wiersema et al, 2005b;Wiersema et al, 2006;Benikos and Johnstone, 2009;Johnstone et al, 2010b;Johnstone and Galletta, in press). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The response inhibition (Barkley, 1997;Quay, 1997) and cognitive energetic models (Sergeant, 2000;Sergeant, 2005) have lent themselves readily to consideration using ERP tasks/methodology. Studies examining the effect of energetic factors on inhibitory processing report at least partial support for the Cognitive Energetic Model (Wiersema et al, 2005b;Wiersema et al, 2006;Benikos and Johnstone, 2009;Johnstone et al, 2010b;Johnstone and Galletta, in press). …”
Section: Discussionmentioning
confidence: 99%
“…In a study with fast and slow presentation of a Go/Nogo task, the relationship between P3 amplitude and Go RT indicated poor effort allocation in the slow condition, with a reduced Nogo-N2 in the fast condition for children with co-morbid AD/HD and ODD, but not an AD/HD-alone group (Wiersema et al, 2006). Using fast, medium and slow event-rates in a cued Go/Nogo task, Benikos and Johnstone (2009) reported a reduced P2 across event-rates, reflecting inefficient suppression of sensory activation, and reduced Nogo-P3 in the fast condition, linked to inhibition problems, in AD/HDcom.…”
Section: Interaction With Energetic Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it was found that the control group made more errors at the slow than medium event-rate, whereas the AD/HD group made more errors at the medium than slow eventrate. This result is surprising considering performance deficits in AD/HD most commonly occur to slow event-rates (Sonuga-Barke et al, 2010;Wiersema et al, 2006b). However, as energetic state is both idiosyncratic and task-dependent, the findings of the present study may be attributable to the unique task requirements of the flanker task (Sonuga-Barke et al, 2010).…”
Section: Task Performancementioning
confidence: 98%
“…Also the state regulation account (Sergeant, 2005;van der Meere, 2005), an influential explanatory account of ADHD, which is derived from the cognitive-energetic model (Sanders, 1983), states that individuals with ADHD have difficulties in maintaining and regulating an optimal energetic arousal/activation state. Research in this respect revealed convincing behavioural and psychophysiological support for disrupted energetic state regulation in ADHD during task execution (Börger & van der Meere, 2000; for a meta-analysis, see Metin, Roeyers, 20 Wiersema, van der Meere, & Sonuga-Barke, 2012;Sergeant, 2005;Sonuga-Barke et al, 2010;Wiersema, van der Meere, Roeyers, Van Coster, & Baeyens, 2006).…”
Section: Discussionmentioning
confidence: 99%